2013
DOI: 10.4049/jimmunol.1300321
|View full text |Cite
|
Sign up to set email alerts
|

Igs Expressed by Chronic Lymphocytic Leukemia B Cells Show Limited Binding-Site Structure Variability

Abstract: Ag selection has been suggested to play a role in chronic lymphocytic leukemia (CLL) pathogenesis, but no large-scale analysis has been performed so far on the structure of the Ag-binding sites (ABSs) of leukemic cell Igs. We sequenced both H and L chain V(D)J rearrangements from 366 CLL patients and modeled their three-dimensional structures. The resulting ABS structures were clustered into a small number of discrete sets, each containing ABSs with similar shapes and physicochemical properties. This structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…Taken together, the present findings offer a novel perspective to BcR antagonism40 as an attractive therapeutic strategy for CLL, targeting the BcR structure rather than the signalling initiated by BcR triggering. Homology models of CLL BcR IGs previously suggested that receptors from different subsets, as well as non-stereotyped cases, might be clustered according to the combining site similarity41. It will be of extreme interest to see if this insight can be confirmed with experimental structures, thus allowing to design bioactive antagonists that can simultaneously target different subsets of patients carrying stereotyped receptors rather than individual CLL cases.…”
Section: Discussionmentioning
confidence: 96%
“…Taken together, the present findings offer a novel perspective to BcR antagonism40 as an attractive therapeutic strategy for CLL, targeting the BcR structure rather than the signalling initiated by BcR triggering. Homology models of CLL BcR IGs previously suggested that receptors from different subsets, as well as non-stereotyped cases, might be clustered according to the combining site similarity41. It will be of extreme interest to see if this insight can be confirmed with experimental structures, thus allowing to design bioactive antagonists that can simultaneously target different subsets of patients carrying stereotyped receptors rather than individual CLL cases.…”
Section: Discussionmentioning
confidence: 96%
“…It would be interesting to determine the affinity of these overlapping subclones in comparison to high-abundant non-overlapping clones. Marcatili and coworkers (62) used BCR repertoires from a large number of CLL patients to cluster the receptors into groups with similar sequence properties that potentially can be used for prognostics. Alternatively, one can compare repertoires across patients to identify consistent Ab sequence features (63).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of RosettaAntibody for repertoire analysis requires, first and foremost, the availability of high-quality paired VH and VL sequence data for each antibody; second, significant computational resources for efficient execution of large-scale computational modeling of antibody repertoires; and, finally, an appropriate suite of informatic tools and statistical metrics suitable for repertoirelevel comparisons. Such a pipeline enables the study of the physicochemical properties of antibody repertoires important for disease and autoimmunity (9,18,28) on a 3D level at the site of antigen contact.…”
Section: Significancementioning
confidence: 99%